1981
DOI: 10.1093/nar/9.15.3873
|View full text |Cite
|
Sign up to set email alerts
|

Cell-cycle-dependent dissociation of histone H1 from chromatin in nuclei of P. polycephalum

Abstract: The dissociation curves of histone Hi from chromatin in interphase and metaphase nuclei from Physarum polycephalum have been determined using CaC12 as dissociating agent. Hi is less strongly bound to metaphase chromosomes than to interphase chromatin. However, no differences could be detected in the binding of Hi to early S, late S or G2 phase chromatin. The number of CaCl2 molecules involved in binding one Hi molecule to chromatin was reduced from 5 in interphase to 4 in metaphase. The non-electrostatic contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1982
1982
1990
1990

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Mohberg & Rusch later (1970) published an amino acid composition for Physarum band 1 that was essentially correct although marred by the presence of an "unidentified acidic amino acid" that can now be seen to be due to oxidation during the hydrolysis (Corbett, 1979). Similar amino acid analyses of Physarum histone HI from plasmodia have been published by Tyrsin et al (1977a), Fischer & Laemmli (1980), and Cruikshank & Walker (1981). A comparison of the Physarum histone H1 amino acid analysis published here (Table III) with an amino acid analysis of calf thymus HI (Johns, 1976) clearly shows the similarity, but there are also substantial differences.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Mohberg & Rusch later (1970) published an amino acid composition for Physarum band 1 that was essentially correct although marred by the presence of an "unidentified acidic amino acid" that can now be seen to be due to oxidation during the hydrolysis (Corbett, 1979). Similar amino acid analyses of Physarum histone HI from plasmodia have been published by Tyrsin et al (1977a), Fischer & Laemmli (1980), and Cruikshank & Walker (1981). A comparison of the Physarum histone H1 amino acid analysis published here (Table III) with an amino acid analysis of calf thymus HI (Johns, 1976) clearly shows the similarity, but there are also substantial differences.…”
Section: Discussionsupporting
confidence: 81%
“…Band 4 was shown to contain two components. The amino acid composition of HI was determined and has been confirmed in several laboratories (Matthews & Bradbury, 1982; Fischer & Laemmli, 1980; Cruikshank & Walker, 1981; Cote et al, 1982). While we have found the CaCl2 extraction method very useful for studies of histones HI and H4, it has been criticized by others (Fischer & Laemmli, 1980;Gurley et al, 1978), and we have found variable yields of histone H3.…”
mentioning
confidence: 80%
“…Following digestion of D. discoideum nuclei and nucleoli with micrococcal nuclease, two populations of mononucleosomes are produced (23,(25)(26)(27)(28). One population containing 146 bp DNA corresponds to the core particle found in all eukaryotes.…”
Section: _mentioning
confidence: 99%
“…2% TCA) and in having 20.5% acidic amino acids. Lysine-rich, major nucleoproteins containing between 14 and 19% glutamic and aspartic acids have been described in Physarum polyceiphalum (23)(24)(25)(26). Similar proteins isolated from Saccharomyces cerevisae have been called HMG proteins (27,28) or Hi (29)(30)(31)(32)(33)(34)(35), although their role in chromatin is unknown.…”
Section: Introductionmentioning
confidence: 99%